Grazing strategies, animal performance and environmental sustainability in intensive pasture-based milk production systems - Batalha, Camila Delveaux Araujo (2018)
In Brazilian livestock, and its diverse ways of production, the management of grazing animals is known as the lowest return on investment on land use opportunities. Nevertheless, among different types of milk production systems, it is noted that the use of pasture grazing is a common feature between them. Thus, to achieve profitability and maintain system sustainability, the identification of the most adequate and efficient pasture management practices, can maximize production per cow and production per unit area. The low efficiency of this method of production, also classifies the national livestock as the major source of environmental pollution due the emission of pollutants, such as greenhouse gases and nitrogen. The adoption of pasture management techniques respecting forage physiological limits and increasing digestibility of nutrients, can reduce the excretion of nutrients and the production of methane per kilo of milk produced on the environment. The objectives of this thesis were to investigate metabolic variables, greenhouse gas emissions and animal performance for dairy cows grazing elephant grass subjected to rotational stocking strategies. Chapter 1: In this study was to evaluate two strategies of grazing management: pre-grazing targets of 95% versus maximum canopy light interception (LI). In intensive pasture-based milk production systems, the management based on LI95% allows lactating cows to have access to pastures with lower proportion of stems, with higher proportions of young leaves better chemical composition and perform an efficient grazing with lower forage losses. Therefore, the LI95% pasture management strategy results in higher energy intake, higher milk production per cow, higher stocking rates of pasture and higher milk yield per area. Also, the strategy allows the decrease of methane emissions per net energy intake when comparing to management based on LIMax. However, dietary N use efficiency did not increase with this management practice. Chapter 2: The objective of the second study was to evaluate the effects of paddock allocation time (a.m. vs. p.m.) on milk production, ruminal variables and efficiency of N use of mid-lactation dairy cows. In intensive pasture-based milk production systems, allocating cows on new paddocks on p.m. time has no effect on forage intake and milk production of grazing mid-lactation cows. However, the higher content of nonstructural carbohydrate of forage from p.m. pastures increases the yield of microbial protein, decreases milk urea nitrogen and tends to increase the yields of milk protein and milk casein compared to a.m. pastures. Throughout this thesis there were an improvement on nutritive value of forage adopting LI95% as a pre- grazing target and forage grazed at p.m. Therefore, the time of allocation on paddock should be used along with LI95% as fine-tune in intensive pasture-based milk production systems.